PENDEKATAN INTEGRATIF UNTUK MERANCANG KURIKULUM MATA PELAJARAN EKONOMI DI SEKOLAH MENENGAH - Nazaruddin Ali Basyah (Al-Hisab: Jurnal Ekonomi Syariah, 2020)
ABSTRACT Education has an important and effective role in the development of a nation. Various studies in many countries have found the strength of the relationship between education and the level of development of these nations. This strong relationship is shown by various economic and socio-cultural indicators. Education that has the ability to facilitate change is education of quality, and relevant to the needs of the entire community. To accelerate the improvement of student achievement in an effective, continuous and comprehensive manner, the government should not only focus on physical development alone but need to focus more on aspects that have a big impact on student achievement such as teacher quality, teaching methods and leadership in schools. The weakness of students is in applying theory to solving economic problems in the questions asked during the (national exam). Students cannot relate economic concepts and theories to the questions being asked. Students are also very weak in answering questions on the microeconomic and macroeconomic sections which contain a combination of economic concepts and mathematical formulas. A teaching method that can assist and encourage students in understanding economic concepts is indispensable. ABSTRAK Pendidikan mempunyai peranan penting dan efektif dalam pembangunan suatu bangsa. Berbagai kajian di banyak Negara mendapati kekuatan hubungan antara pendidikan dengan tingkat pembangunan bangsa-bangsa tersebut. Hubungan yang kuat itu ditunjukkan oleh berbagai indikator ekonomi dan sosial-budaya. Pendidikan yang mempunyai kemampuan memfasilitasi perubahan adalah pendidikan yang berkualitas, dan relevan dengan keperluan seluruh masyarakatnya. Untuk mempercepat perbaikan prestasi pelajar secara efektif, terus menerus dan menyeluruh, pemerintah tidak boleh hanya memberi fokus kepada pembangunan fisik semata-mata tetapi perlu lebih memberikan fokus kepada aspek yang memberi impak besar kepada prestasi pelajar seperti kualitas guru, metode pengajaran dan kepemimpinan di sekolah. Kelemahan pelajar yaitu di dalam pengaplikasian teori bagi penyelesaian masalah ekonomi di dalam soal yang ditanya semasa (ujian nasional). Pelajar tidak dapat mengaitkan konsep dan teori ekonomi dengan soal yang ditanyakan. Para pelajar juga amat lemah di dalam menjawab soal bahagian mikro ekonomi dan makro ekonomi yang mengandung gabungan antara konsep ekonomi dan rumus matematik. Satu metode pengajaran yang boleh membantu dan mendorong para pelajar di dalam memahami konsep-konsep ekonomi sangat diperlukan. Kata Kunci: Perancangan, Prinsip, Pengajaran, Ekonomi, Sekolah Menengah Atas